Impact of Political Factors on Construction Contract Termination: Empirical Evidence From Ghana (AFRICAN JOURNAL OF APPLIED RESEARCH, 2025)
Purpose: This study aims to identify the political factors that lead to the termination of construction contracts in Ghana.Design/Methodology/Approach: A quantitative research design was employed, utilising purposive and random sampling techniques to collect data from 315 respondents, comprising project managers, procurement officers, contract managers, architects, engineers, quantity surveyors, and lecturers from Technical Universities in Ghana. Data were analysed using factor analysis, structural equation modelling (SEM), and confirmatory factor analysis (CFA) to explore the effects of political factors on contract termination.Findings: The results indicate that political factors, including corruption, government violations of clauses, executive leadership changes, poor governance, and a lack of political will, significantly contribute to construction contract terminations. These factors lead to project delays, disputes, and ultimately terminations, highlighting the need for improved governance and risk mitigation strategies in the construction industry.Research Limitation: The study is limited to the construction industry in Ghana and may not account for industry-specific dynamics in other countries.Practical Implication: Suggested measures addressing political instability, improving governance, and minimising political interference could significantly reduce contract terminations in Ghana’s construction sector.Social Implication: There is a need for policy reforms and governance improvements in Ghana’s construction sector. By addressing political instability and promoting transparency, contract terminations could be minimised, leading to better infrastructure development.Originality/Value: This study introduces empirically validated political variables, such as executive leadership change, government clause violations, and a lack of political will and continuity, that expand existing knowledge on construction contract termination.
Keywords: Contract. construction. political factors. project deliverables. termination